Kinematic differences in elite-level American male and female javelin throwers - LeBlanc, M.; Mooney, R. G. (The Engineering of Sport 5, Volume 1, 2004)
Elite-level American female javelin throwers throw less than 70% of the distance their male counterparts throw due primarily to their smaller javelin release velocity. The purpose of this study was to investigate if other kinematic differences exist during the final release phase. The two longest legal throws were analyzed for each of the nine finalists in the men`s and women`s competition at the 2003 National Championships. During the final release phase, each thrower landed on their right foot (RTD), planted their left foot (LTD) and released the javelin (REL). Twenty-one body and three javelin landmarks were digitized and standard DLT methods were used to obtain 3D data from before RTD past REL. Comparisons were made between the males` and females` trunk backward/forward angle and the javelin`s attitude, release, and attack angles. All comparisons were made using t-tests with a = 0.025 (a = 0.05, adjusted for multiple comparisons). The trunk`s backward/forward lean angle was significantly different for the males and females at RTD (-19.8° and -24.0°, respectively) and at LTD (-12.5° and -20.9°, respectively). However, their trunk angles were not significantly different at REL (22.3° and 20.9°, respectively). The javelin`s attitude angle was significantly different at RTD (26.3° and 35.7°, respectively), at LTD (31.3° and 40.3°, respectively), and at REL (33.8° and 41.8°, respectively). Curiously, the release angle of the javelin was not significantly different (32.3° and 32.2°, respectively). The females` larger backward lean angle at RTD and LTD may contribute to the larger attitude angle, while at REL, similar trunk angles may relate to similar release angles. The combination of angles at REL led to much larger attack angle for the females (9.6° versus 1.8°) which, in general, diminishes the throw distance. These differences may partially explain the large differences in the distance thrown by the males and females.